Тhe questions of formation of future teachers’ pedagogical competence in the process of modeling situations with preventive orientation (Pedagogy of Higher and Secondary Education, 2013)
Kulinka Y. Тhe questions of formation of future teachers’ pedagogical competence in the process of modeling situations with preventive orientation.The article examines the issues of formation of future teachers’ pedagogical competence, technology in the simulations preventive orientation, the basic approaches to the problem of modeling pedagogical situations are depicted here, the difficulties are described which are appearing in the process of designing and the example of situations with preventive orientation in the study of general pedagogy is given.
Keywords: professional pedagogical teacher’s training; pedagogical competence; modeling; pedagogical situations; modeling pedagogical situations; groups of situations with preventive orientation